Menopause: risk factors - Álvarez García , Miriam; Hernández Castillo, Caridad; González González, Adeanis (Revista Minerva, 2021)
The quality of health services in today’s world has become a matter of interest for health professionals, always in search of obtaining better results for the population, providing the minimum of risks for the improvement of their health and adequate use of the resources available to carry out the actions, especially in the care of women and that is why the programs seek to prevent and educate. Menopause is a normal stage of life, just as puberty is the stage of the last menstrual cycle, but symptoms can begin several years before age and can last for months or persist for several years. Causing changes in the levels of estrogen and progesterone, female hormones that reproduce in the ovaries. As estrogen production decreases, ovulation and menstruation occur often, eventually stopping. But it can stop earlier due to illness or hysterectomy. The objective of the research is to characterize the risk factors in the incidence of menopause the methodology used was prospective, with randomized clinical trials and systematic analysis, investigations of various designs and articles by various authors were reviewed. It was concluded that from the selected sample the highest percentage with risk factors was the range of 35 to 45 years and it was shown that various risk factors contribute significantly to the poor quality of life of menopausal women.